Assessment of long-distance running performance in elite male runners using onset of blood lactate accumulation - Abe, D.; Sakaguchi, Y.; Tsuchimochi, H.; Endo, M.; Miyake, K.; Miyahiro, S.; Kanamaru, K.; Niihara, S. (Journal of Physiological Anthropology, 1999)
The purpose of this study was to evaluate the relationship between onset of blood lactate accumulation (OBLA) and long-distance running performance in order to examine whether OBLA can be a good predictor of long-distance running performance even in elite male runners with similar performance levels. Eleven highly-trained male long-distance runners participated in this study. The average running velocities of the individuals` running performance were 5.918 ± 0.084 m·s-1 and 5.672 ± 0.095 m·s-1 for 5000 m (V5000) and 10000 m (V10000), respectively. The blood lactate concentrations and heart rate responses were measured immediately after field running, and the average value of running velocity corresponding to OBLA (VOBLA) was 5.447 ± 0.132 m·s-1. Variations of these three velocities expressed as a coefficient of variance (CV) ranged from 1.4 to 2.4%. A strong inverse relationship between heart rate corresponding to OBLA (HROBLA) and performance was observed (r=-0.709, p<0.02 for V5000 and r=-0.830, p<0.01 for V10000), while there was a lack of significant relationship between VOBLA and performance (r=0.293, NS for V5000 and r=0.130, NS for V10000). Furthermore, the average value of HROBLA obtained in this study (174.5 ± 8.2 b·min-1) was quite similar to that of the heart rate threshold reported by some previous researchers. In conclusion, VOBLA alone could not explain the small variation of long-distance running performance, and HROBLA should be used in place of VOBLA for evaluating long-distance running performance in elite runners with quite similar performance levels.